UTILIZATION OF MACKAREL TUNA IN LIQUID ORGANIC FERTILIZER AGAINST PHOSPHORUS AND CALCIUM CONTENT - Adharani, Nadya; Agustin, Cici; Sulthoniyah, Siti Tsaniyatul Miratis (Chanos Chanos, 2023)
Mackarel tuna is one of the fish that is quite abundant in Banyuwangi, its existence in the Java and Bali seas is found throughout the month, therefore the use of mackerel tuna fish into processed food products is often made by the community. In addition to being a valuable product, mackerel tuna fish bones can be processed into other products that are useful in agriculture, namely organic liquid fertilizer. This study was conducted on a laboratory scale with four different treatments (length of fermentation time) including 5, 10, 15, and 20 days, where each treatment was repeated 4 times. The purpose of the study was to find out the best phosphorus and calcium content from four different treatments. The results of the study found that the best fermentation period of liquid organic fertilizer was on the 20th day of fermentation with a value of phosphorus (P) content of 0.091%, calcium (Ca) of 0.377%.